Thickening of The Blekok Finger Bone (Ardeola speciosa) - Tabrany, Aghnia Nafi’Audi; Wijaya, Monica Tasya Risma; Jannah, Umi Miftakhul (Proceeding International Conference on Science and Engineering, 2020)
Ardeola speciosa, also known as the Blekok bird, is an Aves group that has the Ardeola order. Ardeola speciosa has a size of about 46 cm, long strands of white fur on the front and back of the head to the back. The back color is blacker. Lower body and pure is white wings. It has a gray and yellow beak with a black tip. The beak is yellow with a black tip. And has yellow feet. Each leg on Ardeola speciosa has four toes consisting of segments on each finger. On this occasion we will examine the fingers of the Blekok bird. This research was used to examine the thickening of the finger bones, before being examined the finger bones were cleaned until clean and visible bones, then cut each finger in a transverse position carefully so that the part under study was not damaged. Then it is observed in each bone whether there is thickening in the bone wall.